2022
DOI: 10.1007/978-3-030-94583-1_15
|View full text |Cite
|
Sign up to set email alerts
|

NP Satisfiability for Arrays as Powers

Abstract: We study the satisfiability problem of symbolic finite automata and decompose it into the satisfiability problem of the theory of the input characters and the monadic second-order theory of the indices of accepted words. We use our decomposition to obtain tight computational complexity bounds on the decision problem for this automata class and an extension that considers linear arithmetic constraints on the underlying effective Boolean algebra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Finally, although quite challenging, it would be interesting to extend our interpolation results also to array theories combined with cardinality constraints, similar to those introduced, e.g., in [2], [27].…”
Section: Further Related Work and Conclusionmentioning
confidence: 95%
“…Finally, although quite challenging, it would be interesting to extend our interpolation results also to array theories combined with cardinality constraints, similar to those introduced, e.g., in [2], [27].…”
Section: Further Related Work and Conclusionmentioning
confidence: 95%
“…Our work is related to a long tradition of research in decision procedures for set constraints. These have found applications in the verification and analysis of programs [1,2,27,34]. In [18], the authors studied the complexity of deciding set constrains in the style of Jònnson and Tarski's framework of Boolean algebra with operations.…”
Section: Related Workmentioning
confidence: 99%
“…We believe that such results are of interest because they compose with other constructions that preserve NP membership. In particular, in a recent analysis of array theories [34] we observed that the fragment of combinatory array logic [12] corresponds to the theory generated by a power structure with an arbitrary index set and with QFBAPA constraints on the index set. Given that [34] shows NP complexity for such product, it is natural to ask how far we can extend NP satisfiability results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that such results are of interest because they compose with other constructions that preserve NP membership. In particular, in a recent analysis of array theories [45] we observed that the fragment of combinatory array logic [13] corresponds to the theory generated by a power structure with an arbitrary index set subject to QFBAPA constraints. Given that [45] shows a NP complexity bound for such product, it is natural to ask how far we can extend NP satisfiability results.…”
Section: Introductionmentioning
confidence: 99%